Progressive Left Diaphragmatic Eventration Manifesting as Respiratory Failure in an Elderly Patient with Chronic Obstructive Pulmonary Disease: A Case Report - Morris Lintong Barimbing; R.A. Tuty Kuswardhani (MEDICINUS, 2026)
Background: Diaphragmatic eventration (DE) is a rare condition characterized by the abnormal elevation of an anatomically intact hemidiaphragm. In adults, it is often asymptomatic. However, in elderly patients with significant pulmonary comorbidities such as chronic obstructive pulmonary disease (COPD), the progression of DE can precipitate acute, life-threatening respiratory decompensation.Case presentation: A 70-year-old man with COPD, hypertension, and chronic kidney disease presented with worsening dyspnea, cough, and gastrointestinal symptoms that were refractory to COPD therapy. Serial chest radiographs revealeddramatic progression from a previously asymptomatic elevated left hemidiaphragm to complete diaphragmatic eventration with visceral herniation, resulting in severe impairment of lung function. Surgical plication via video-assisted thoracoscopic (VATS) was advised; however, the patient developed acute psychological distress upon learning the surgical plan, followed by sudden cardiac arrest and death. This case illustrates the fatal convergence of structural respiratory compromise, chronic pulmonary disease, and acute emotional stress as a cardiac trigger.Conclusions: Progressive DE should be considered in the differential diagnosis of unexplained respiratory failure in COPD patients, especially when unresponsive to standard therapy. Serial imaging is crucial for diagnosis, and the management of psychological stress is a vital component in the care of critically ill geriatric patients.